2010
DOI: 10.1002/sia.3199
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and structural changes of porous templates obtained by anodising aluminium in phosphoric acid electrolyte

Abstract: Ordered anodic aluminium oxide (AAO) films were first prepared by anodising in a phosphoric acid electrolyte and then studied extensively and characterised by field emission gun-scanning electron microscopy (FEG-SEM), X-ray diffraction, Raman and infrared spectroscopy at a macroscopic scale. These analyses showed that the as-prepared AAO film is in fact amorphous, partially hydrated and that its initial global chemical composition can be described, in agreement with previous works, as: Al 2 O 3 , 0.186AlPO 4 ·… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…Figure 1 illustrates the structure of the anodized layer on aluminum prior to sealing and changes that occur during sealing. The chemical and phase composition of the anodized layer on aluminum has been a subject of much interest [64][65][66][67][68][69][70][71][72]. From analysis of these numerous reports on the subject, there appears to be a consensus that the porous anodized layer on aluminum prior to sealing is predominantly comprised of amorphous alumina [64,69,73,74], some boehmite (AlOOH) [66,75,76], and aluminum oxide compounds whose actual compositions are determined by the bath electrolyte anion chemistry.…”
Section: Structure and Composition Of Anodized Oxide Layer On Anodizementioning
confidence: 99%
See 2 more Smart Citations
“…Figure 1 illustrates the structure of the anodized layer on aluminum prior to sealing and changes that occur during sealing. The chemical and phase composition of the anodized layer on aluminum has been a subject of much interest [64][65][66][67][68][69][70][71][72]. From analysis of these numerous reports on the subject, there appears to be a consensus that the porous anodized layer on aluminum prior to sealing is predominantly comprised of amorphous alumina [64,69,73,74], some boehmite (AlOOH) [66,75,76], and aluminum oxide compounds whose actual compositions are determined by the bath electrolyte anion chemistry.…”
Section: Structure and Composition Of Anodized Oxide Layer On Anodizementioning
confidence: 99%
“…Hashimoto et al [82] recently investigated the local structure around aluminum atoms in anodic alumina using nuclear magnetic resonance spectroscopy, critiqued earlier studies on the subject matter, and reported that aluminum cations coordinated with oxygen anions in three types of coordination; AlO4 (tetra-coordination), AlO5 (penta-coordination), and AlO6 (octahedralcoordination), and that penta-coordination was predominant while the proportion of octahedrally coordinated (AlO6) units decreased with removal of physisorbed water. They [82] also evaluated the range of ratios of each mode of coordination to be 30%-40% for AlO4, 50%-60% for AlO5, and 4%- The chemical and phase composition of the anodized layer on aluminum has been a subject of much interest [64][65][66][67][68][69][70][71][72]. From analysis of these numerous reports on the subject, there appears to be a consensus that the porous anodized layer on aluminum prior to sealing is predominantly comprised of amorphous alumina [64,69,73,74], some boehmite (AlOOH) [66,75,76], and aluminum oxide compounds whose actual compositions are determined by the bath electrolyte anion chemistry.…”
Section: Structure and Composition Of Anodized Oxide Layer On Anodizementioning
confidence: 99%
See 1 more Smart Citation
“…The porosity of the anodic films grown on aluminium substrates depends on various operating conditions, related to the anodization electrolyte and to the applied electrical parameters, as well as the substrate itself. Pure substrates thus allow anodic aluminium oxide (AAO) templates with highly ordered porosities to be produced; these latter have been extensively studied . In contrast, complex and tortuous porosities are usually obtained for multiphase aluminium alloys, eg, aeronautical AA 2XXX or 7XXX …”
Section: Introductionmentioning
confidence: 99%
“…The inorganic AlOOH particle is one of the most widely used inorganic flame retardant additives due to its demonstrated properties such as being tasteless, non-toxic, heat resistance, and non-volatile. It decomposes at 400 °C [3] according to the following reaction [4]: 2AlOOH (s) → Al 2 O 3 (s) + H 2 O (g) …”
Section: Introductionmentioning
confidence: 99%